"How Philly Moves": from urban branding to kinesthetic sympathy through an aesthetic of blur. Issue 2 (2nd July 2016) - Bruce, Caitlin Frances
ABSTRACT: This article investigates the production and mural aesthetic of the "How Philly Moves" mural, photography, and dance project. The project enables scholars to trace different intensities of dialogic encounter throughout its process, exploring how the remediation of a dance event leaves kinesthetic and rhythmic traces. This project, works against commodifying tendencies while within dominant frameworks and cultivates what I call "kinesthetic sympathy, " an ethic and aesthetic of rhythmic resonance that acknowledges the ongoingness of the subject while inspiring a sense of kinetic impact in the viewer or participant, part of a spectrum of affective connection constituted through rhythmic intimacies.